Promoting O. viverini-free Traditional Food Consumption to Reduce Infection and Prevent Reinfection of O. viverrini in Khok Prong Sub-district, Phetchabun Province - Pumidonming, Wilawan; Grongang, Dulyatad; Sangkaeo, Khamphon; Thammatrakun, Nanthaphon; Kotanon, Panumus (Area Based Development Research Journal, 2020)
Consumption of traditional raw food prepared from cyprinid fish including plara, plasom and pla jom has been reported a risk factor for Opisthorchis viverrini infection. The objectives of this project stressed 1) develop O. viverini-free traditional diets; 2) promote consumption of the O. viverini-free menu and health education and 3) evaluate the efficacy of this promotion in controlling infection and reinfection of O. viverini. This project was undertaken in Khok Prong sub-district, Wichian Buri district, Phetchabun province in 2015-2019. The procedure was divided into 3 phases: Phase 1 identifies risk factors and O. viverrini infection rate in the target sub-district, laboratory diagnosis for O. viverini infection, treatment of infected cases, and reports infection rates to community stakeholders and planning prevention and control policies. Phase 2 develops the O. viverini-free traditional menu suitable for the infected communities. Phase 3 determines infection and re-infection rates, measure changes in dietary behavior in the target group. The program achieved a reduced infection rate from 28.7% to 7.2%. Cooperative work and combination methods with campaigns for consuming parasite-free traditional meals reduced infection in high prevalence communities. Conclusion, consumption of a parasite-free traditional meal can have a major impact in controlling O. viverini in endemic areas where traditionally raw fish is preferred.